[PP.21.07] SERUM URIC ACID LEVELS AND 10-YEAR RISK OF FATAL CARDIOVASCULAR DISEASE. A PROSPECTIVE STUDY. (September 2017) - Kallistratos, M.; Giannitsi, S.; Poulimenos, L.E.; Iliou, K.; Koukouzeli, A.; Kouremenos, N.; Chamodraka, E.F.; Pagoni, S.; Kyfnidis, K.; Pittaras, A.; Manolis, A.J.
Abstract : Objective: Serum uric acid (SUA) is associated with many traditional cardiovascular risk factors such as arterial hypertension. Our aim was to investigate the relationship of SUA levels with the 10-year risk of fatal cardiovascular disease. Design and method: We prospectively enrolled 113 subjects (mean age 53 ± 12 years) presented for evaluation in the antihypertensive clinic. In all subjects routine blood chemistry, including SUA determination, echocardiographic examination, office and 24 h ambulatory blood pressure (BP) monitoring were obtained. In all patients data regarding lifestyle habits (smoking, alcohol consumption and exercise) were recorded. The 10-year risk of fatal cardiovascular disease was evaluated by using the SCORE chart for countries with low CVD risk based on the following risk factors: age, sex, smoking, systolic blood pressure, and total cholesterol. Results: Mean average 24 hours systolic blood pressure (SBP) was 124 ± 13 mmHg, mean 24 hours average diastolic blood pressure (DBP) was 75 ± 10 mmHg while mean total cholesterol was 210 ± 36 mg/dl. From 113 subjects included in the study only 26 (23%) were hypertensives. Pearson and spearman analysis showed that SUA levels were significantly and positively associated with the average 24 hours systolic and diastolic blood pressure levels (r = 0.35, p < 0.0001 for SBP) and (r = 0.33, p < 0.0001 for DBP) respectively. Furthermore the kruskal Wallis analysis revealed that SUA levels were significantly associated with 10-year risk of fatal cardiovascular disease (p < 0.0001). Specifically patients with 10-year risk <5%, 5–10%, >10%, presented SUA levels 4.4 ± 0.9 mg/dl, 5.2 ± 1 mg/dl and 6.4 ± 0.1 mg/dl respectively (p < 0.0001). Conclusions: Subjects with lower SUA levels presented lower BP levels as well as 10-year risk of fatal cardiovascular disease and vice versa. SUA levels were significantly associated with blood pressure levels and 10-year risk of fatal cardiovascular disease. The fact that this study included mainly normotensives, shows that SUA levels are also associated with subjects presenting normal or high normal blood pressure levels.